Superconductivity in CuAl2-type Co0.2Ni0.1Cu0.1Rh0.3Ir0.3Zr2 with a high-entropy-alloy transition metal site. Issue 3 (4th March 2021) - Mizuguchi, Yoshikazu; Kasem, Md. Riad; Matsuda, Tatsuma D.
ABSTRACT: Research on high-entropy-alloy (HEA) superconductors is a growing field in material science. In this study, we explored new HEA-type superconductors and discovered a CuAl2 -type superconductor Co0.2 Ni0.1 Cu0.1 Rh0.3 Ir0.3 Zr2 with a HEA-type transition metal site. A superconducting transition was observed at 8.0 K after electrical resistivity, magnetization, and specific heat measurements. The bulk characteristics of the superconductivity were confirmed through the specific heat measurements. The discovery of superconductivity in HEA-type Co0.2 Ni0.1 Cu0.1 Rh0.3 Ir0.3 Zr2 will provide a novel pathway to explore new HEA-type superconductors and investigate the relationship between the mixing entropy and superconductivity of HEA-type compounds. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: We report on the material design, synthesis, and observation of a superconducting transition at 8.0 K in new high-entropy-alloy-type compound with a CuAl2 -type structure, Co0.2 Ni0.1 Cu0.1 Rh0.3 Ir0.3 Zr2 .